Phase I study of BAY 94‐9027, a PEGylated B‐domain‐deleted recombinant factor VIII with an extended half‐life, in subjects with hemophilia A - Coyle, T. E.; Reding, M. T.; Lin, J. C.; Michaels, L. A.; Shah, A.; Powell, J. (Journal of thrombosis and haemostasis, 2014)
Summary Background BAY 94‐9027 is a B‐domain‐deleted recombinant factor VIII (rFVIII) with site‐specific attachment of poly(ethylene glycol) that has shown an extended half‐life in animal models of hemophilia. Objectives To assess the pharmacokinetics and safety of BAY 94‐9027 after single and repeated administration in subjects with severe hemophilia A. Patients/Methods This 8‐week, prospective, multicenter, open‐label, phase I trial was conducted in 14 subjects aged 21–58 years with FVIII of < 1%, ≥ 150 days of exposure to FVIII, and no history of FVIII inhibitors. After a ≥ 3‐day washout, subjects received a single dose of sucrose‐formulated rFVIII (rFVIII‐FS) (cohort 1 [n = 7], 25 IU kg−1; cohort 2 [n = 7], 50 IU kg−1) for a 48‐h pharmacokinetic (PK) study. After another ≥ 3‐day washout, cohort 1 received twice‐weekly BAY 94‐9027 at 25 IU kg−1 (16 doses), and cohort 2 received once‐weekly BAY 94‐9027 at 60 IU kg−1 (nine doses). A 168‐h PK study was performed after the first and last BAY 94‐9027 doses. Results BAY 94‐9027 showed equivalent recovery and an improved PK profile vs. rFVIII‐FS, with a half‐life of ~ 19 h (vs. ~ 13.0 h for rFVIII‐FS). BAY 94‐9027 was well tolerated, and no immunogenicity was observed. Conclusions This phase I study demonstrates that BAY 94‐9027 has an extended half‐life in subjects with hemophilia A and, after multiple dosing, was well tolerated with no immunogenicity during the 8‐week trial. A phase III study in a larger number of subjects is underway to fully characterize how this prolonged half‐life will permit less frequent prophylaxis dosing for patients with hemophilia.